2018
DOI: 10.1158/1538-7445.am2018-3831
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 3831: Development of near-infrared photoimmunotherapy targeting GD2-positive neuroblastoma

Abstract: Background: Neuroblastoma (NB) is a primary malignant tumor of the peripheral sympathetic nervous system. Despite the recent advances in the treatment of NB, patients with high-risk NB still have poor prognosis. Immunotherapy using anti-GD2 monoclonal antibody (mAb), which binds to disialoganglioside GD2 on the surface of NB cells, has recently become a standard treatment for high-risk NB. However, the therapeutic efficacy of anti-GD2 mAb is insufficient in many clinical trials. Therefore, the enhancement of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Nouso et al showed that the administration of anti-GD2-IRDye700DX followed by NIR-PIT significantly suppressed cell viability compared to an anti-GD2 monoclonal antibody. Thus, their results showed NIR-PIT as a promising anti-tumour strategy to enhance the therapeutic efficacy of anti-GD2 immunotherapy for high-risk NB ( 91 ). Maruoka et al ( 92 ) hypothesised that the administration of IL-15 with cancer cell-targeted NIR-PIT could increase anti-tumour host immunity.…”
Section: Intra-operative Loco-regional Treatmentsmentioning
confidence: 99%
“…Nouso et al showed that the administration of anti-GD2-IRDye700DX followed by NIR-PIT significantly suppressed cell viability compared to an anti-GD2 monoclonal antibody. Thus, their results showed NIR-PIT as a promising anti-tumour strategy to enhance the therapeutic efficacy of anti-GD2 immunotherapy for high-risk NB ( 91 ). Maruoka et al ( 92 ) hypothesised that the administration of IL-15 with cancer cell-targeted NIR-PIT could increase anti-tumour host immunity.…”
Section: Intra-operative Loco-regional Treatmentsmentioning
confidence: 99%
“…In particular, NIR-PIT causes direct (Figure 3-panel B) and indirect (Figure 3-panel C) cell killing because the cell membrane rupture releases tumourspecific antigens into the TME and promotes dendritic cell (DC) maturation, resulting in the presentation of cancer-specific antigens on DCs to naive T cells. At the American Association for Cancer Research meeting in 2018, Hiroshi Nouso et al [49] presented the use of NIR-PIT with an anti-GD2-IR700 as a promising anti-tumour strategy to enhance the therapeutic efficacy of anti-GD2 immunotherapy for high-risk NB. They evaluated the anti-tumour effect of anti-GD2-IR700 on three human NB cell lines, showing that the administration of anti-GD2-IR700 significantly suppressed the cell viability compared to anti-GD2 mAb when combined with NIR light irradiation.…”
Section: Near-infrared Photoimmunotherapy (Nir-pit)mentioning
confidence: 99%